A literature review of the nexus between migration and internationalization. Issue 3 (3rd April 2021) - Hatzigeorgiou, Andreas; Lodefalk, Magnus
Abstract : Protectionism and anti-globalization tides have been rising already before the COVID-19 pandemic, with Brexit and the China-U.S. trade war, as two examples. A continued disruption to global trade, investment and value chains could worsen global development. Economic recovery will require restoring firms' ability to trade, offshore and invest globally. To achieve this, it will be useful to understand the role of migration for foreign trade, investment and other aspects of internationalization. In this paper we review and discuss over 100 papers published about migrants' roles on international trade, foreign direct investment and offshoring. Although the evidence suggests that migration facilitates trade and internationalization, we also note substantial gaps and inconsistencies in the existing literature. The aim of this paper is to encourage further research and assist policymakers in their efforts to promote economic recovery including internationalization.